2020
DOI: 10.1002/anie.202001364
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Silanol Triad in the Zeolite Catalyst SSZ‐70

Abstract: Nests of three silanol groups are located on the internal pore surface of calcined zeolite SSZ‐70. 2D 1H double/triple‐quantum single‐quantum correlation NMR experiments enable a rigorous identification of these silanol triad nests. They reveal a close proximity to the structure directing agent (SDA), that is, N,N′‐diisobutyl imidazolium cations, in the as‐synthesized material, in which the defects are negatively charged (silanol dyad plus one charged SiO− siloxy group) for charge balance. It is inferred that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…By carefully correlating the paired HAADF‐STEM and iDPC images, it can be concluded that Ir atoms appear in several locations, including sites at the 10MR window between the 12MR supercages and in the 12MR supercages, as illustrated in the Supporting Information, Figure S6. This is consistent with a recent work on the identification of the location of the triad silanol species in SSZ‐70, a related pure‐silica zeolite to the MWW zeolite studied in this work . In the as‐synthesized Ir@MWW‐OSDA sample, the Ir precursor is surrounded by the organic template molecules, encapsulated in the cages and cavities inside the MWW zeolite crystallites.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…By carefully correlating the paired HAADF‐STEM and iDPC images, it can be concluded that Ir atoms appear in several locations, including sites at the 10MR window between the 12MR supercages and in the 12MR supercages, as illustrated in the Supporting Information, Figure S6. This is consistent with a recent work on the identification of the location of the triad silanol species in SSZ‐70, a related pure‐silica zeolite to the MWW zeolite studied in this work . In the as‐synthesized Ir@MWW‐OSDA sample, the Ir precursor is surrounded by the organic template molecules, encapsulated in the cages and cavities inside the MWW zeolite crystallites.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with ar ecent work on the identification of the location of the triad silanol species in SSZ-70, arelated puresilica zeolite to the MWW zeolite studied in this work. [23] In the as-synthesized Ir@MWW-OSDAsample,the Ir precursor is surrounded by the organic template molecules,e ncapsulated in the cages and cavities inside the MWW zeolite crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…A shoulder at 3728 cm −1 assigned to the intracrystalline silanols was also observed, and its intensity increased with the increasing content of disordered stacking structure. A previous study demonstrated the disordered MWW zeolite material contained two kinds of silanols on the layer surface, namely the single terminal Si‐OH and a cluster of 3 Si‐OH (Figure S13) [9a, 18] . Thus, the presence of more intracrystalline defects in MWW‐C 6 ‐SAR60 and MWW‐C 7 ‐SAR62 was consistent with the high contents of disordered stacking structure in these two materials (Figure S7).…”
Section: Figuresupporting
confidence: 67%
“…10,11 A potential overlap of1 H MAS NMR signals originating from BAS and hydrogen-bonded silanol groups has not been previously addressed. This may be in part due to the hitherto existing difficulties in separating SiOH from bridging hydroxyl groups, Si−O(H)−Al, in 1 H MAS NMR spectra.…”
mentioning
confidence: 99%